EFEKTIVITAS PELAKSANAAN PERATURAN DAERAH PROVINSI GORONTALO NOMOR 10 TAHUN 2014 TENTANG KAWASAN TANPA ROKOK (KTR) - Yuliska Filastri Ruruh; Nurwita Ismail; Arifin Tumuhulawa (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
This research analyzes the effectiveness of Gorontalo Province Regional Regulation No. 10 of 2014 concerning Smoke-Free Areas (KTR), identifies influencing factors, and formulates improvement efforts. Employing a normative empirical method with a sociology of law approach, the study examines the regulation's implementation in society. The findings indicate that the implementation of the KTR Regional Regulation is not yet effective. Smoking activities persist in KTR areas without significant action from authorities, despite stipulated sanctions. Factors hindering effectiveness include low public awareness, insufficient support from the government and law enforcement, minimal public participation, and limited funding and infrastructure. To enhance the effectiveness of the KTR Regional Regulation, the research recommends socialization efforts, inter-agency coordination, the establishment of a supervisory team, strict law enforcement, and clear sanctions for violators. Furthermore, it is crucial to increase public education and guidance regarding the dangers of smoking and the urgency of KTR. Recommendations for the public include complying with the KTR Regional Regulation, particularly in health facilities and schools. The Regional Government is expected to continue its socialization efforts. Effective enforcement of the KTR Regional Regulation is anticipated to improve the community's quality of life by making it healthier and free from cigarette smoke.